Early Ambulation to Prevent Delirium After Long-Time Head and Neck Cancer Surgery - Kim, Jeong Heon; Lee, Yoon Se; Kim, Yong Han; Cho, Ki Ju; Jung, Young Ho; Choi, Seung-Ho; Nam, Soon Yuhl; Kim, Sang Yoon (Frontiers in Surgery, 2022)
Objective: Postoperative delirium is known to have various adverse effects on head and neck surgery patients. This study was designed to identify possible risk factors of delirium following long periods of head and neck cancer surgery and to help prevent postoperative delirium. Methods: We enrolled 197 patients who underwent long-time (>6 hours) head and neck surgery at the Asan Medical Center from January 2017 to December 2018 in this study. Clinical covariates that may be associated with delirium were analyzed retrospectively using univariate and multivariate analyses. Results: Delirium occurred in 18 patients (9.1%). Within the first 7 days, 16 patients (88.9%) experienced delirium. Upon univariate analysis, delirium was associated with old age (≥75, p = 0.001), past neurological history (p = 0.019), time to ambulation (p = 0.014), and postoperative hospital day (p = 0.048). In multivariate analysis, old age (≥75, odds ratios (OR) 6.16, CI 2.00–19.00, p = 0.002), time to ambulation (OR 1.04, CI 1.01–1.07, p = 0.017), and past neurological history (OR 5.26, CI 1.09–25.37, p = 0.039) were significant risk factors associated with postoperative delirium. Conclusions: Older patients or patients with neurologic history must be attended with care, especially early after surgery. Encouraging early ambulation might lower the incidence of postoperative delirium and, subsequently, reduce adverse effects. This result could benefit patients by helping them avoid undesirable outcomes.